A standardized postoperative bowel regimen protocol after spine surgery - Yue, John K.; Krishnan, Nishanth; Wang, Albert S.; Chung, Jason E.; Etemad, Leila L.; Manley, Geoffrey T.; Tarapore, Phiroz E. (Frontiers in Surgery, 2023)
Objectives: Spine surgery is associated with early impairment of gastrointestinal motility, with postoperative ileus rates of 5-12%. A standardized postoperative medication regimen aimed at early restoration of bowel function can reduce morbidity and cost, and its study should be prioritized. Methods: A standardized postoperative bowel medication protocol was implemented for all elective spine surgeries performed by a single neurosurgeon from March 1, 2022 to June 30, 2022 at a metropolitan Veterans Affairs medical center. Daily bowel function was tracked and medications were advanced using the protocol. Clinical, surgical, and length of stay data are reported. Results: Across 20 consecutive surgeries in 19 patients, mean age was 68.9 years (standard deviation (SD)=10; range 40-84). Seventy-four percent reported preoperative constipation. Surgeries consisted of 45% fusion and 55% decompression; lumbar retroperitoneal approaches constituted 30% (10% anterior, 20% lateral). Two patients were discharged in good condition prior to bowel movement after meeting institutional discharge criteria; the other 18 cases all had return of bowel function by postoperative day (POD) 3 (mean=1.8-days, SD=0.7). There were no inpatient or 30-day complications. Mean discharge occurred 3.3-days post-surgery (SD=1.5; range 1-6; home 95%, skilled nursing facility 5%). Estimated cumulative cost of the bowel regimen was 17 on POD 3. Conclusions: Careful monitoring of return of bowel function after elective spine surgery is important for preventing ileus, reducing healthcare cost, and ensuring quality. Our standardized postoperative bowel regimen was associated with return of bowel function within 3 days and low costs. These findings can be utilized in quality-of-care pathways.